2010
DOI: 10.3109/0142159x.2010.509766
|View full text |Cite
|
Sign up to set email alerts
|

Can students adequately evaluate the activities of their peers in PBL?

Abstract: The results prove that peers are able to provide reliable and valid information about a student's active participation in the tutorial group, if at least four peer ratings are attainable, out of a group of eight students. In conclusion, the M-PARS is a valid and reliable instrument.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
1
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(35 citation statements)
references
References 23 publications
1
32
1
1
Order By: Relevance
“…These correlations could indicate that we are dealing with only one type of student tutorial activity. However, a confirmatory factor analysis in a previous study (Kamp et al 2011) has proved that there are indeed three different factors with regard to the three types of tutorial student activity. Furthermore, in the model one factor (constructive activities) predicts the score on the multiple choice unit test and the other factor (collaborative activities) predicts the score on the group assignment.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These correlations could indicate that we are dealing with only one type of student tutorial activity. However, a confirmatory factor analysis in a previous study (Kamp et al 2011) has proved that there are indeed three different factors with regard to the three types of tutorial student activity. Furthermore, in the model one factor (constructive activities) predicts the score on the multiple choice unit test and the other factor (collaborative activities) predicts the score on the group assignment.…”
Section: Discussionmentioning
confidence: 99%
“…In a previous study (Kamp et al 2011) the Maastricht Peer Activity Rating Scale (M-PARS) was developed with which students can evaluate three main aspects of tutorial peer activity: a peer's constructive, collaborative and motivational contributions to the tutorial group. This study also demonstrated that, students are able to evaluate their peers on these three aspects in a reliable and valid way and that, only four evaluations per student are needed for a reliable judgment.…”
Section: Peer Evaluationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Aunque hay evidencias de que la evaluación del ABP es más dificultosa (Smits et al, 2002), ciertos estudios han mostrado la confiabilidad de la evaluación realizada por los propios compañeros (Kamp et al, 2011). Hay que planificar mejor si queremos modificar conocimientos y actitudes, pero sigue habiendo resultados contradictorios en áreas como medicina, que muestran que las diferencias de rendimiento fueron mínimas en el periodo de residencia entre ABP y método tradicional (Distlehorst et al, 2009).…”
Section: Discussionunclassified
“…PBL is defined as a form of learning that involves small groups of six to ten learners working together in teams to comprehend and resolve a situation derived from a scenario. [7] Context-based learning (CBL) is a version of PBL which involves small groups of 10 to 14 students working with a faculty tutor to discuss situations that nurses typically encounter in practice. [8] CBL is based on the assumption that nursing is holistic and nurses appreciate the life context of their patients in providing care either in assisting people who are experiencing health problems or providing health promotion programs to enable patients to maintain their wellness.…”
Section: Introductionmentioning
confidence: 99%